An algorithm to predict the connectome of neural microcircuits - Reimann, Michael W.; King, James G.; Muller, Eilif B.; Ramaswamy, Srikanth; Markram, Henry (Frontiers in Computational Neuroscience, 2015)
Experimentally mapping synaptic connections, in terms of the numbers and locations of their synapses and estimating connection probabilities is still not a tractable task, even for small volumes of tissue, In fact, the 6 layers of the neocortex contain thousands of unique types of synaptic connections between the many different types of neurons, of which only a handful have been characterized experimentally. Here we present a theoretical framework and a data-driven algorithmic strategy to digitally reconstruct the complete synaptic connectivity between the different types of neuron in a in a small well-defined volume of tissue – the micro scale connectome of a neural microcircuit. By enforcing a set of established principles of synaptic connectivity and leveraging interdependencies between fundamental properties of neural microcircuits to constrain the reconstructed connectivity, the algorithm yields three parameters per connection type that predict the anatomy of all types of biologically viable synaptic connections. The predictions reproduce a spectrum of experimental data on synaptic connectivity not used by the algorithm. We conclude that an algorithmic approach to the connectome can serve as a tool to accelerate experimental mapping, indicating the minimal dataset required to make useful predictions, identifying the datasets required to improve their accuracy, testing the feasibility of experimental measurements, and making it possible to test hypotheses of synaptic connectivity.